STRATEGI PENINGKATAN KUALITAS KINERJA SUMBER DAYA MANUSIA PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA BONTANG - Eko Mashudi (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
This study aims to analyze strategies for improving the quality of human resource performance at the Regional Disaster Management Agency (BPBD) of Bontang City through digital transformation and disaster management training. The research employs a qualitative, descriptive, and exploratory approach. Data were collected through interviews, participatory observation, and document analysis of BPBD Bontang. Data analysis was conducted using Spradley’s method. The findings reveal that the transformation strategy was implemented through enhancing employee competencies, recruiting civil servants under the PPPK scheme, providing disaster response training for community volunteers, digitalizing work systems, strengthening institutional structures, and fostering multi-stakeholder partnerships. The application of disaster information systems, digital archiving, and the launch of an official website has accelerated bureaucratic processes and improved public communication.